Wierność w czasach cyfrowej zarazy, czyli o prawach i obowiązkach małżeńskich w dobie sztucznej inteligencji i nowych technologii: in the time of digital plague, or marital rights and duties in the age of artificial intelligence and new technologies - Ogrodnik-Kalita, Agnieszka (PRAWO i WIĘŹ, 2024)
The author deals with the impact of artificial intelligence and new technologies on the form and scope of the legal duty of fidelity, which derives directly from Art. 23 of the Family and Guardianship Code. In addition to the important terminological issues, the author focuses on two aspects of the problem under discussion. The first is a specific case of emotional infidelity, in which the spouse establishes a relationship with a third party by means of remote communication. The other and more interesting case concerns the legal assessment of the emergence of warm feelings in one of the spouses towards the artificial intelligence with which the spouse communicates. In particular, the possibility of attributing guilt to a spouse who engages in such behavior is discussed.